Endometrial evaluation with methylene blue staining in patients with normal hysteroscopy - Goel, Alka; Gupta, Pooja; Singh, Akansha; Singh, Khushboo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Normally, endometrium comprises of non-absorptive epithelium and does not take up stain. Conventional staining with methylene blue is explained on the basis of existence of apoptotic cells in endometrium. Methods: Of 50 patients of unexplained infertility, AUB, recurrent pregnancy loss were randomly selected and included in the study. Those with abnormal ultrasound and history of tuberculosis were excluded. Conventional hysteroscopy was performed using normal saline as distending medium and in those with grossly normal endometrium were subjected to staining with 5% methylene blue instilled trans cervically. After 5 min, irrespective of the size and pattern, focal dark blue stained areas were considered abnormal and randomly biopsied. Incidence of endometritis in both groups was compared after histopathological examination. Results: Of total 50 patients, histopathological report of only one patient with dark blue staining had evidence of endometritis. Rest had no evidence, of which 73.5% had light blue or unstained areas and 26.5% showed dark blue staining. No statistically significant difference was found between histopathological reports and light or dark blue staining (p=0.28). When percentage stained area was considered more than 50% only to be positive, sensitivity was 100%, specificity 94%, PPV 25% and NPV 100%. False positives were 75% and no false negatives were observed. Although p values improved but still statistically insignificant. Conclusions: Present study failed to establish any significant correlation between staining pattern and detection rate of endometritis. With no Indian studies published on chromohysteroscopy so far, role of methylene blue in detection of subtle endometrial changes in modern gynaecology in Indian subpopulation is yet to be established.